Artery reopening is required for the neurorestorative effects of angiotensin modulation after experimental stroke. (December 2016) - Alhusban, Ahmed; Kozak, Anna; Eldashan, Wael; Ergul, Adviye; Fagan, Susan
Abstract Background Blood flow restoration with fibrinolysis and thrombectomy is recommended to limit injury in stroke patients with proximal artery occlusion. Angiotensin receptor blockers have been shown to be neuroprotective in models of permanent and temporary occlusion, but the benefits on expression of trophic factors have been seen only when the artery is reopened. It is possible that early artery opening with endovascular intervention may increase the likelihood of identifying an effective combination therapy for patients. Methods Normotensive male Wistar rats were subjected to mechanical middle cerebral artery occlusion (either temporary or permanent), followed by randomization to receive candesartan (0.3 mg/kg IV) or saline. Functional outcome, infarct size, and biochemical changes were assessed 24 h after ischemia induction. Results Lack of reperfusion blunted candesartan induced neuroprotection (p < 0.05) and reduced the improvement of functional outcome (p < 0.05). With reperfusion, candesartan increased mature BDNF expression in the contralateral hemisphere (p < 0.05) and activated prosurvival (Akt-GSK3-β) signaling (p < 0.05). Without reperfusion, candesartan significantly reduced VEGF expression and MMP activation and increased NOGO A expression, creating an environment hostile to recovery. Conclusion Candesartan induced pro-recovery effects are dependent on the presence of reperfusion.